Renal and endothelial biomarkers in Chagas disease in the Brazilian Amazon region: Early indicators of kidney injury and disease progression - Alba Regina Jorge Brandão; Jorge Augusto de Oliveira Guerra; Jessica Vanina Ortiz; Débora Raysa Teixeira de Sousa; Gabriela Maciel Alencar; Nádelly Karoline Martins Derze; João Victor Campelo de Queiroz; Joana Bader Sadala Brandão; Lara Isabelli Oliveira da Silva; Cássia Camila de Oliveira Araújo; Silvia Cassia Brandão Justiniano; Lucely Paiva Rodrigues da Silva; et al. (PLoS ONE, 2026)
Chagas disease (CD) has impact on Amazon public health, where oral transmission is frequently related to acute cases. This peculiarity influences clinical severity and immunological responses, highlighting the need to investigate novel biomarkers for early detection of renal and endothelial dysfunctions, since conventional methods are limited in identifying subclinical renal injury. The aim of this study is to investigate the expression of biomarkers of renal and endothelial injury in acute and chronic CD in the Brazilian Amazon. A cross-sectional study was conducted between 2021 and 2023 at the Fundação de Medicina Tropical Doutor Heitor Vieira Dourado (FMTHVD), Manaus, Amazonas, Brazil. Seventy-eight native Amazonian patients diagnosed with CD were evaluated and grouped by disease clinical phase: G1a (acute pre-treatment), G1b (acute post-treatment), G2a (chronic indeterminate), and G2b (chronic cardiac). Blood and urine levels of SYN-1, ANG-2, MCP-1, and NGAL were quantified using ELISA test and correlated with creatinine, urea, proteinuria, and glomerular filtration rate (GFR). Biomarkers were elevated across CD phases, despite routine renal function parameters remaining within normal ranges. Urinary NGAL and MCP-1 levels were significantly elevated in G1, reflecting early renal inflammation. SYN-1 was elevated in patient groups compared with controls, indicating early endothelial damage, while ANG-2 showed high variability with limited subgroup discrimination in G2, suggesting progressive endothelial dysfunction. Overall, G1, especially G1b, exhibited a more severe inflammatory and tissue injury profile, whereas G2 groups were similar to controls. Conventional markers did not correlate with the biomarkers, suggesting their sensitivity in detecting early subclinical injury. The novel biomarkers studied showed an association with different phases of CD and signs of endothelial and renal dysfunction, suggesting potential to aid in the detection of subclinical changes related to the disease.